Efficacy and safety of 88% phenol application versus cryotherapy in repigmentation of idiopathic guttate hypomelanosis: A comparative study - Rajegowda, Harish Muddanahalli; Kalegowda, Deepadarshan; Madegowda, Shashikumar Basavapura; Rangarajaiah, Ambika C (Journal of Pakistan Association of Dermatologists, 2020)
Background Idiopathic guttate hypomelanosis (IGH) is a common, acquired dermatosis characterized by multiple, round or oval, hypopigmented to depigmented macules. A variety of therapies with variable success are described, despite that, the treatment remains still unsatisfactory and therapeutic challenge for dermatologists. Â Objective The objective of this study is to compare the safety & efficacy of 88% phenol application & cryotherapy in repigmentation of IGH macules. Â Materials and Methods A total of 30 patients with more than 10 IGH macules were selected. For each enrolled patient 88% phenol was applied to 5 IGH macules and single cryotherapy for 3-5 seconds was applied for another 5 IGH macules once in a month till the repigmentation for maximum of 3 applications. Patients were assessed monthly for 3 months for the side effects and improvement in pigmentation. The degree of improvement in pigmentation was assessed using a grading system, <25%- no response (grade-1), 26-50% minimal (grade-2), 51-75% good (grade-3) and >75% excellent response (grade-4). Â Results A total of 25 patients completed the study. At the end of the treatment period, out of 125 macules treated with short contact cryotherapy 75(60%) macules showed excellent response & 20(16%) macules showed good response. In phenol group, out of 125 macules 37(29.6%) & 29(23.2%) macules showed excellent & good improvement in pigmentation respectively, with p-value<0.05. Side effects like persistent scabbing, ulceration were more common with 88% phenol application compared to cryotherapy. Â Conclusion Short contact cryotherapy of 3-5 seconds was found to be more efficacious and safe compared to therapeutic wounding with 88% phenol in inducing pigmentation of IGH macules. Â